2015
DOI: 10.5144/0256-4947.2015.403
|View full text |Cite
|
Sign up to set email alerts
|

Hourglass bladder after ileocystoplasty (case report)

Abstract: Narrowing of the anastomotic area between the bowel segment and urinary bladder is known as “hour-glass bladder.” This report describes a rare case of hourglass bladder deformity occurring post-ileocystoplasty in a 14-year-old male. We describe the essential steps that should be taken during bladder augmentation to avoid such a complication, along with a discussion of the relevant literature. This case emphasizes the need to strictly adhere to the steps of augmentation cystoplasty to avoid this technical compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In 2009, Vaidyanathan et al described a patient with an hourglass bladder as a late complication of suprapubic cystostomy [6]. In 2015, Alhazmi reported a case occurring after ileocystoplasty [7]. Congenital hourglass bladder is an extremely rare anomaly, warranting consideration in the differential diagnosis with conditions such as bladder duplication, bladder diverticula, and other urological malformations.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Vaidyanathan et al described a patient with an hourglass bladder as a late complication of suprapubic cystostomy [6]. In 2015, Alhazmi reported a case occurring after ileocystoplasty [7]. Congenital hourglass bladder is an extremely rare anomaly, warranting consideration in the differential diagnosis with conditions such as bladder duplication, bladder diverticula, and other urological malformations.…”
Section: Discussionmentioning
confidence: 99%
“…These configurations are now generally accepted as cautionary tales when discussing modern augmentation cystoplasty techniques. [14][15][16] Surgical revisions for augmentation cystoplasty have been reported scarcely in the urologic literature. Vajda et al reported on five patients who underwent prior augmentation, with more than half as gastrocystoplasty.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%